Glomus tympanicum : a report of two cases. - Subha, Sethu Thakachy; Raman, Rajagopalan; Prepageran , Narayanan (Malaysian Medical Association., 2005)
Two cases of glomus tympanicum tumor of the middle ear stage 'type A' according to Fisch classification, are presented due to their rarity in this part of the world. These tumors were excised by end aural tympanotomy approach and there has been no recurrence in both patients to date.